Scientific Basics of Forming Human Quality and Perfection to Ensure Holistic Sustained Development - Suvorov, Nickolay; Suvorova, Iryna (European Journal of Sustainable Development, 2015)
The general substance underlying the existence and development of the Universe and Man is energy. Energy is the unique and universal nature of all being. Everything is reduced to the amount and quality of energy. We were the first in the world to scientifically substantiate harmony as the universal criterion of the quality of energy of inner and outer interaction, optimality, perfection of energy-information images and systems of diverse nature. The harmony help solve the problem of forming high quality and perfection of human personality. Harmony is the key technology of creation, which God introduced when creating the Universe. The principles of harmony and holism are the basic components of Cosmo theory, the theory of development of the Universe and Man. In concentrated form, the theoretical studies dedicated to harmony and forming a new and perfect human being are presented in the book by NIKOLAI SUVOROV: " ? Perfect Man", International Publishers ERA, 2014, 300 pp. Embracing harmony creates conditions for sustained development-evolution of any human being, nation and civilisation as a whole. We believe that in the EU countries it would be practical to set up R&D and perfection training centres for studying and practically applying harmony. Key words: Harmony, quality, perfection.